2022
DOI: 10.3390/rs14030464
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Land Reclamation Activities Using Landsat Observations—An Example in Shanghai and Hangzhou Bay

Abstract: At present, reclamation—changing ocean areas into inland land cover type for human usage—is one of the major methods for expanding land area around the world to alleviate the problem of land shortage. Thus, reclamation activities play an important role in land area extension. In recent years, reclamation projects have been active in eastern China. However, research on how to determine the initiation of reclamation activity remains very limited. Thus, a method of tracking reclamation activities was proposed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In comparison to natural impacts, human activities often exert more intense and complex influences on the water color and morphological characteristics. For example, bridge construction projects can significantly alter SPM concentrations over several kilometers [27], while deposit-promoting projects swiftly change landcover types [28], affecting nearby erosion-deposition patterns, as well as SPM distribution. Figure 1 shows three regions of interest within Hangzhou Bay, as follows: A.1 was selected to assess the observational capabilities for SPM distributions.…”
Section: Study Areamentioning
confidence: 99%
“…In comparison to natural impacts, human activities often exert more intense and complex influences on the water color and morphological characteristics. For example, bridge construction projects can significantly alter SPM concentrations over several kilometers [27], while deposit-promoting projects swiftly change landcover types [28], affecting nearby erosion-deposition patterns, as well as SPM distribution. Figure 1 shows three regions of interest within Hangzhou Bay, as follows: A.1 was selected to assess the observational capabilities for SPM distributions.…”
Section: Study Areamentioning
confidence: 99%
“…To address the lack of available land, one of the critical methods of increasing land area in many countries is reclamation, which involves converting open ocean areas into inland areas for human use. In modern society, there is an increase in nearshore and offshore engineering [3][4][5][6][7], which inevitably pollutes the marine environment and influences water quality, for example, in terms of suspended particulate matter (SPM), orthophosphate phosphorus (PO 4 P), and dissolved inorganic nitrogen (DIN), especially SPM [8][9][10]. Driven by wind, waves, and ocean currents, SPM and nutrient salts continuously drift and spread, posing a serious threat to the marine ecological balance [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…GF-1 WFV has a high spatial resolution (16 m), but short time series (from 2013 to now) [12]. Landsat satellites have the proper image width (185 km), spatial resolution (30 m), and time series (from 1972 to now) [3,31,38]. Previous studies have demonstrated the feasibility of using Landsat satellites to observe water quality changes in the Pearl River Estuary region [10,16,20,33].…”
Section: Introductionmentioning
confidence: 99%